Manipulating aqueous chemistry environments in extractive metallurgy - Govan, Premesh (Department of Chemical Engineering, 2014)
The Anglo Research Nickel (ArNi) process is a novel extractive metallurgical process that arose out of the need to develop a processing route for the recovery of nickel from lateritic ore deposits that is both economical and environmentally acceptable.